2010
DOI: 10.1007/s10995-010-0698-0
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health Beliefs and Health Behavior in Early Pregnancy

Abstract: Folate-supplementation significantly reduces the risk of neural tube defects. The aim of this research was to reveal associations between health beliefs and folate -supplementation as well as other elements of health behavior among Hungarian women early in their pregnancy. Three-hundred and seven women in early pregnancy completed the second part of Health and Illness Scale. Factor structure of health beliefs was established and associations of factors with pregnancy planning, folate-intake, vitamin-intake, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the total sample, the overall frequency of all types of health-related behavior (the total score on HRBI) was found to be positively related to both internal, powerful others and chance HLC, strikingly, with the highest correlation coefficients for powerful others HLC. This finding questions the universality of the claim that external HLC should be linked to unfavorable outcomes in health-related behavior [38], [39]. In this context, it is interesting to note that some studies also reported the associations between powerful others HLC and desirable health-related behavior.…”
Section: Discussionmentioning
confidence: 91%
“…In the total sample, the overall frequency of all types of health-related behavior (the total score on HRBI) was found to be positively related to both internal, powerful others and chance HLC, strikingly, with the highest correlation coefficients for powerful others HLC. This finding questions the universality of the claim that external HLC should be linked to unfavorable outcomes in health-related behavior [38], [39]. In this context, it is interesting to note that some studies also reported the associations between powerful others HLC and desirable health-related behavior.…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, pregnant women desire positive health messages around healthy eating and weight management during pregnancy, with a focus on what they can/should do, as opposed to what they should not do [ 40 ]. Advice can be incorporated into a locus of control model, whereby shifting health beliefs and health locus of control from external causes to internal dimensions may support healthy behavioral tendencies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential positive effects for the health of the woman and her neonate, pregnancy is an opportune time for probiotic use. Both beliefs and knowledge seem to strongly affect the mother’s behaviour [ 6 ]. Review of the literature shows that ingestion of probiotics (combination of strains of Lactobacillus and Bifidobacterium ) for a limited period of time during (late) pregnancy appears to be low risk, as it does not increase the rate of adverse pregnancy outcomes and seems to be well tolerated [ 30 ].…”
Section: Introductionmentioning
confidence: 99%